2014
DOI: 10.1017/s1474746413000602
|View full text |Cite
|
Sign up to set email alerts
|

Policy Paradigm Shift and the Changing Role of the State: The Development of Social Policy in China since 2003

Abstract: Since 2003 the rapid development of China's social policy has aroused much academic interest. This research places the development of social policy in China's political and economic context, focusing on the changing role of the state in making and implementing social policy. Based on the policy paradigm theory, this article builds up a framework to analyse the shift of social policy paradigms in post-Mao China, examining the changing role of the Chinese state in social welfare and social development. It argues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Although the economic transition was gradual and incremental, it swiftly led to the destruction of old social security institutions (Chan, Ngok, & Phillips, 2008). Only in recent years has China seen a prominent expansion of social policies, in response to rising social instability and the need for the party-state to maintain political legitimacy (Ngok & Huang, 2014).…”
Section: Evolution Of the Social Security System In Urban Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Although the economic transition was gradual and incremental, it swiftly led to the destruction of old social security institutions (Chan, Ngok, & Phillips, 2008). Only in recent years has China seen a prominent expansion of social policies, in response to rising social instability and the need for the party-state to maintain political legitimacy (Ngok & Huang, 2014).…”
Section: Evolution Of the Social Security System In Urban Chinamentioning
confidence: 99%
“…Despite the authoritarian nature of the Chinese political system, public attitudes have become increasingly important considerations in policy-making. It is found that even in political systems without contested elections or an independent civil society, authoritarian governments such as the Chinese authorities are still sensitive to public sentiments in order to avoid social instability and the erosion of political legitimacy (Duckett & Wang, 2013;Ngok & Huang, 2014). Therefore, soliciting citizens' views on the existing system and their expectations for improvement is very crucial to inform China's ongoing social security reforms.…”
Section: Introductionmentioning
confidence: 99%
“…He attaches great importance to and always emphasizes the vital role of developing socialist productive forces. For the development of productive forces and the importance of achieving social justice, Deng Xiaoping believes that: "The superiority of socialism, the most fundamental is to greatly develop social productive forces, and gradually improve the people's material and spiritual life" [6]. It can be seen that Deng Xiaoping realized that only by vigorously developing socialist productive forces can we improve the living standards of the broad masses of the people and achieve social justice, so as to further demonstrate the superiority of the socialist system and fundamentally consolidate the socialist system.…”
Section: Developing Productivity: Materials Prerequisites For Social Jmentioning
confidence: 99%
“…Guo 2013; Goodman 2013), exhibiting a logic fitting of neoliberal philosophy experienced in the global context as well. By the mid-1990s, however, growing levels of inequality would again begin to reshape attitudes not only around inequality, but also around State responsibility for public services and welfare provision, bringing about another policy paradigm shift in the early 2000s (Ngok and Zhu 2010;Zhang 2012;Ngok and Huang 2014).…”
Section: Decentralisation and State Capacity In Welfare Provisionmentioning
confidence: 99%